PENERAPAN PEMBELAJARAN KOOPERATIF PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KOMPETENSI DASAR MENGINDETIFIKASIKAN TINDAKAN, MOTIF DAN PRINSIP EKONOMI MATA PELAJARAN IPS KELAS VII DI MTS SABILIL MUKARROMAH BERCAK CERMEE BONDOWOSO SEMESTER GENAP - Zainul Munawwir (STKIP PGRI SITUBONDO, 2014)
Problem posing method of learning is that students are less able to present a problem. Results of some studies also menyabutkan that one material that Shiva is considered to be difficult in solving the story (Muliyardi, 2001: 2). Design of this research is the PTK to collaborate with teachers who do 2 sklus. In the last four stage PTK is planning, action, observation and reflection. Primary data using secondary data replication tests with interviews. The study used must target value or KKM (Criterion Kutubtasan Minimal) determine success criteria for menganilisis data. Based on the findings in chapter IV can be saved as follows: Pnenerapan learning cooperative problem posing can increase student learning outcomes achieve a gain of 91% basic competence mengdentifikasikan actions, motives and economic principles of subjects ips Sester 1 class VII MTs Sabilil Mukarromah BercakCermee Bondowoso.